MEASURING COMMUNITY PHARMACISTS’ KNOWLEDGE AND ATTITUDE OF PRESCRIBING ERRORS - SHOROUQ AL-OMOUSH; DERAR H ABDEL-QADER; SAHAR JARADAT; ALIA SALEH; SALIM HAMADI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to investigate knowledge, attitudes, and practices among community pharmacists regarding prescribing errors (PEs) in Jordan. Methods: This was a cross-sectional survey-based study conducted in Jordan among community pharmacists over 8 weeks. A structured questionnaire was designed, validated, and sent to community pharmacists to assess their knowledge, attitudes, and practices (KAP) toward PEs. Results: Of 752 participants approached, 398 were included in the data analysis. The mean scores of KAP were: 6.9, 8.1, and 8.5, respectively, all out of 10. Among participants included in this study, 126 (31.7%) showed good knowledge about PEs, 268 (67.3%) demonstrated a positive attitude toward PEs, and 291 (73.1%) showed good practice regarding PEs. Among the participants, 380 (95.5%) showed knowledge about contraindication errors, 369 (92.7%) exhibited knowledge about duplicate errors, and 371 (93.2%) were knowledgeable about wrong strength errors. Furthermore, 67 (16.8%) reported that prescribing a drug at a dose inappropriate for the patient’s renal function was considered an omission error. In addition, approximately one-third of the participants (34.2%) were unable to differentiate between wrong dose errors and wrong frequency errors. More than half of the participants agreed (55.5%) and strongly agreed (17.1%) that pharmacists had an important role to play in identifying and preventing PEs. Conclusion: Pharmacists who participated in this study had a moderate knowledge about PEs; however, their attitude and practice levels seemed positive and good, respectively.